2021
DOI: 10.32434/0321-4095-2021-137-4-58-65
|View full text |Cite
|
Sign up to set email alerts
|

Research into kinetics of filtration drying of alcohol distillery stillage

Abstract: The article describes the results of experimental studies on kinetics of the filtration drying of corn distillery stillage, which has previously proven its effectiveness in drying other crops and various dispersed materials. The experimental data are presented in the form of graphical plots describing the change of material moisture over time depending on the temperature of the drying agent (60, 70, 80 and 900С) and the layer height (40, 80, 120 and 160 mm). The obtained results are analyzed and the changes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Drying of the experimental material was carried out by the energy saving method of filtration drying on a laboratory experimental installation. The method of experiments, measurements, as well as the scheme and operation principle of the laboratory installation are described in the previous work [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drying of the experimental material was carried out by the energy saving method of filtration drying on a laboratory experimental installation. The method of experiments, measurements, as well as the scheme and operation principle of the laboratory installation are described in the previous work [13].…”
Section: Methodsmentioning
confidence: 99%
“…All mentioned application areas require partial or complete drying of BSG, which increases required time for storage, transportation, and its use as a secondary raw material [13].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [19] determined the diffusion coefficient during grain filtration drying, based on the solution to differential equations under the boundary conditions of the first kind. Paper [20] reports the results of experimental studies into the kinetics of filtration drying of corn bards, which has previously proven effective in drying other crops and various dispersed materials. The reported results have been analyzed; the changes occurring on the filtration drying curves depending on the change in the height of the material layer and the temperature of the heating agent have been described.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The dependences obtained by the authors could be used only to predict the kinetics of filtration drying of the materials studied in those works, which are characterized by a certain shape and structural structure of particles. However, the results of the studies reported in [17][18][19][20] relate to specific materials, so their application to other materials that differ in structural structure and shape of particles is impossible due to a large error between experimental and theoretically calculated values. No experimental or theoretical studies into the kinetics of filtration drying of crushed cotton stalks were found in the available literature.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation